ACCOUNTING AND THE S.E.C. (The Accounting Review, 1937)
This article presents cases which are resumes of situations of interest to accountants, arising in the work of the Securities and Exchange Commission. In each instance, a problem appears together with the solution brought about by recommendations of the Commission's staff. The names of registrants do not appear, but if further study of any one or more cases is desired, the names may be secured from the editor of the "Review." The balance sheet of a distilling company showed "Fixed Assets: Property," plant and equipment at cost. The notes and schedules referred to indicated that, of this amount, $48,343.81 represented property "purchased on a lease-purchase contract," was payable as rent, in monthly installments and "at the expiration of the ten-year period legal title is to pass to the purchaser." In the opinion of the Commission's staff, because of the nature of the contract, it was improper to designate on the balance sheet any part of the amount to be expended under the lease-purchase contract as "Property, plant and equipment" before the expiration and fulfillment of the contract.